A comparative study on mutual fund performances of emerging markets in the era of quantitative easing - Tan, Ömer Faruk. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
This study aims to analyze six emerging markets’ equity funds – Turkey, Poland, Taiwan, South Africa, India and Mexico – during the period between January 2009 and October 2014. After the global financial crisis of 2008 came a period of quantitative easing (QE), creating an increase in the money supply and leading to a capital flow from developed countries to developing countries. The stock markets of these selected emerging countries increased dramatically during the era of quantitative easing. In this work, a total of 73 equity funds (11 Turkish Equity Funds, 14 Polish Equity Funds, 15 Taiwanese Equity Funds, 10 South African Equity Funds, 12 Indian Equity Funds, 11 Mexican Equity Funds) are analyzed in order to compare these funds’ performances within this period. In order to measure these funds’ performances, the Sharpe ratio (1966), Treynor ratio (1965), Jensen’s alpha (1968), Sortino ratio (1994) and M2 ratio (1996) methods are used. Jensen’s alpha is also used in identifying selectivity skills of fund managers. Furthermore, the Treynor & Mazuy (1966) and Henriksson & Merton (1981) regression analysis methods are applied to ascertain the market timing ability of fund managers.
Keywords: Quantitative easing (Monetary policy); Mutual funds.